O ensino de empreendedorismo na educação pública: uma análise acerca da concepção docente nos anos iniciais do ensino fundamental no município de Alcantil PB. - Silva, Genilson José da (2018)
The present dissertation analyzes the insertion of entrepreneurship in the initial years of Elementary School in the public network in the municipality of Alcantil in Paraíba. Throughout this investigation we trace a course about the historical materiality of this theme that has its theoretical bases anchored in the Economy and Classical Sociology of the 17th and 18th centuries, in the presuppositions of neoliberalism, in the public policies for education delineated by the United Nations in Brazil, in the foundations of the human capital theory, in the technical education and in the conceptions of reproductive education with highlights to the last decades of the twentieth century. We had as general objective to understand the teaching conceptions about the teaching of entrepreneurship in public basic education. Regarding methodology, we define as epistemological path, historical materialism to apprehend the phenomenon, entrepreneurship interrelated with educational practice and determined by the economicpolitical determinants. In relation to the method of approach and analysis we define the materialist dialectic as the way to construct the concrete thought, from the real concrete, which consisted of three movements mediated by the analytical and empirical categories, the first, a reflection on the historical foundations and philosophical questions about entrepreneurship, the second, the teaching conception about the teaching of entrepreneurship, and the third, the relation of entrepreneurial education with the teaching work and with the schooling of subjects. In the final considerations, we point out that entrepreneurship education unfolds in public education through a partnership between the public and private sectors and constitutes a business management model that ensures the reproductive dynamics of capital through the methodology of entrepreneurship education teaching that stimulates the acquisition of skills and abilities in the teaching-learning process. Regarding the teaching conceptions, we observe that there is an appreciation of the teaching contents of entrepreneurship because of their flexibility and interdisciplinarity. Teachers define the teaching methodology of entrepreneurship education as an innovative, dynamic practice with immediate results focused on the creation of business plans and for insertion in the labor market. However, they did not point out the contradictions in the relation between theory and practice, nor the foundations that reproduce this logic of productivist teaching, excluding and validated in meritocratic aspects. Therefore, this analysis denounces the ramifications of the neoliberal paradigm in public education and requires a deepening on this theme at the national and educational level to understand the articulation between the teaching work process and the training of subjects in public education, considering that the school should not reproduce a model of business management because its essence is not the economic and financial market, but the sociocultural and political formation of subjects based on their social practice.